Effect of crude palm oil consumption on the levels of plasma ß-carotene, malondialdehyde and xanthine oxidase activity of healthy housewives - Yunita Filia Assah; Shinta Wahyu Apriyani; Alim Mahawan Nuryadi; Ardi Kurniawan Makalalag (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Crude palm oil that contains high ß-carotenecan be obtained from mesocarp extraction of Elaesisguneensis Jacq.In the body, the ß-caroteneis converted to vitamin A that has antioxidant activity. Antioxidantscan inhibit lipid peroxidation induced by free radicals or singlet oxygen. It also inhibits the increase of reactive oxygen species (ROS) in the form of anion superoxide and hydrogen peroxide through the xanthine oxidase mechanism.This study aimed to evaluate the effect of crude palm oil consumption on the plasma ß-carotene and malondialdehyde (MDA) levels as well as xanthine oxidase activityof healthy housewives. Twenty-two healthy housewives who met the inclusion and exclusion criteria were involved in this study. Blood plasma samples were taken before and after consuming crude palm oil for two months as much as± 3.58 mL daily.The results showed that consumption of crude palm oil increased the plasma ß-carotene levels of 16 people (72%),and decreased the plasma MDAlevels of 13 people (59%).Meanwhile, thexantin oxidase enzyme activity showed no significantly different (p>0.05). Crude palm oil can increase plasma ß-carotene levels. It can be an alternative natural food source of provitamin A due to the high β-carotene content.